Analisis Pengaruh Field Of View Terhadap Informasi Anatomi CT-Scan Bagian Abdomen - Nurhadi Nurhadi; Abd. Charis Fauzan; Muhammad Helmi Hakim (Universitas Nahdlatul Ulama Blitar, 2026)
This study aims to develop a portable formula milk preservation device prototype using infrared irradiation technology. The materials and components used in this study include a 950 nm infrared LED, a lithium battery, a charging module, a touchscreen switch, an NPN transistor, epoxy resin, and resin hardener. The research was conducted in four stages. The first stage involved designing the electronic circuit layout. The second stage focused on fabricating the device casing using epoxy resin. The third stage consisted of assembling the electronic components into the previously fabricated casing. The final stage involved testing the prototype to evaluate its operating time without recharging. The results of the study produced a portable liquid formula milk preservation device prototype based on infrared technology with the following specifications: an input voltage of DC 3.7–5.5 V, an input current of 1 A, an output voltage of DC 5 V, and an output current of 1 A. The prototype generated infrared radiation with a wavelength of 940 nm, was powered by a 1,550 mAh battery, and was capable of operating continuously for up to 1.5 hours without recharging.